2014
DOI: 10.11604/pamj.2014.18.164.3355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of burnout pattern between hospital physicians and family physicians working in Suez Canal University Hospitals

Abstract: IntroductionThe burnout syndrome is characterized by emotional exhaustion, depersonalization, and low personal accomplishment. It is associated with impaired job performance.MethodsThis descriptive study examined 171 physicians for the presence of burnout and its related risk factors. The evaluation of burnout was through Maslach Burnout Inventory (MBI). The participant was considered to meet the study criteria for burnout if he or she got a “high“ score on at least 2 of the three dimensions of MBI.ResultsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
(41 reference statements)
1
16
3
7
Order By: Relevance
“…Research conducted in Colombia, involving 106 family doctors, showed a high overall risk of burnout syndrome among family doctors [24]. Kotb and colleagues in their study, which included 171 doctors, demonstrated that hospital doctors suffered significantly more from burnout than family doctors [25]. In our research, family doctors have higher stress levels and all three components of burnout syndrome in relation to the hospital doctors, but not significantly.…”
Section: Discussioncontrasting
confidence: 48%
“…Research conducted in Colombia, involving 106 family doctors, showed a high overall risk of burnout syndrome among family doctors [24]. Kotb and colleagues in their study, which included 171 doctors, demonstrated that hospital doctors suffered significantly more from burnout than family doctors [25]. In our research, family doctors have higher stress levels and all three components of burnout syndrome in relation to the hospital doctors, but not significantly.…”
Section: Discussioncontrasting
confidence: 48%
“…This may explain the higher inpatient costs among hospital-based physicians. In addition, a previous study showed that the prevalence of burnout in hospital physicians was significantly higher than in family physicians [ 19 ]. Physicians in hospitals are faced with more-complex, more-stressful, and more-irregular patterns of life [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study also elucidated variables, some of which are new, that are associated with burnout. There is a wide variation in the reported prevalence of burnout among general pediatricians in various locations, ranging between 18 and 46% [1618]. The higher estimate of 46% was reported in 2015 in the US [17], where there has been a sharp rise from a previous report of 35% in 2012 [19].…”
Section: Discussionmentioning
confidence: 99%